El cine de la Guerra Civil y la función de la vanguardia cinematográfica. - Luis Veres (Amnis)
This article is a tour through the achievements of Spanish cinema film on the subject of the Spanish Civil War (1936-1939) in connection with the birth and the consequences of the historical vanguards. Thus, the work is a critical assessment of films from the Republican side to the films of the national side in relation to their parentage avant-garde and its implications for the development of historiographical clichés and rote in the history of Spain.